2021
DOI: 10.1101/2021.05.26.445743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environment, rather thanHematodiniumparasitization, determines collateral disease contraction in a crustacean host

Abstract: Host, pathogen, and environment are determinants of the disease triangle, the latter being a key driver of disease outcomes and persistence within a community. The dinoflagellate genus Hematodinium is detrimental to crustaceans globally – considered to suppress the innate defences of hosts, making them more susceptible to co-infections. Evidence supporting immune-suppression is largely anecdotal and sourced from diffuse accounts of compromised decapods. We used a population of shore crabs (Carcinus maenas), wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Negative controls consisted of DEPC-treated Molecular Biology Grade Water (Sigma Aldrich) in the absence of DNA template to avoid false positives due to contamination. Positive controls consisted of 1 μL DNA purified from the haemolymph of an infected donor crab (Carcinus maenas; Davies et al, 2021). PCR products were visualised using 2 % (w/v) agarose/TBE gels stained with 3 μL Greensafe premium nucleic acid stain (NZYTech, Lisboa, Portugal).…”
Section: Tissue Histologymentioning
confidence: 99%
“…Negative controls consisted of DEPC-treated Molecular Biology Grade Water (Sigma Aldrich) in the absence of DNA template to avoid false positives due to contamination. Positive controls consisted of 1 μL DNA purified from the haemolymph of an infected donor crab (Carcinus maenas; Davies et al, 2021). PCR products were visualised using 2 % (w/v) agarose/TBE gels stained with 3 μL Greensafe premium nucleic acid stain (NZYTech, Lisboa, Portugal).…”
Section: Tissue Histologymentioning
confidence: 99%
“…Using PCR-based methods and Sanger sequencing revealed the Milford Haven and Swansea Bay populations of Crepidula fornicata to be free of these target pathogens (i.e. Interestingly, a study carried out by Davies et al (2021) in Swansea Bay found populations of shore crabs Carcinus maenas, as well as seawater eDNA samples, to be positive for the same parasite taxa screened for in this chapter. This indicates that although these pathogens are present in the environment and other invertebrates, Crepidula fornicata does not appear to be susceptible to them.…”
Section: Discussionmentioning
confidence: 67%
“…3%) it is likely that C. fornicata has become an accidental host in the two study locations and that the principal primary intermediate hosts are probably various native littorinids. Despite shellfish, such as crabs, in the locality being known to be infected with pathogens such as haplosporidians, and microsporidians (Davies et al, 2020(Davies et al, , 2021, C. fornicata appears to lack general vulnerability to these either as main or accidental hosts. This ability to not succumb to disease could be an important reason for its success as an invader.…”
Section: Chapter 6 General Discussionmentioning
confidence: 99%